Analysis of the Effect of Compensation and Motivation on Performance of Employees in the Department of Women's Empowerment Children Protection Population and Family Control of Seluma District - Sudriyanti Putri (Journal of Indonesian Management, 2021)
The purpose of this study to determine the effect ofcompentasionand motivation to the performance of The women empowerment service, child peotection, population control and family planning Board Officer Seluma District. The population in this study is which consists of 65 government apparatur in the The women empowerment service, child peotection, population control and family planning Board Officer Seluma District. This survey research takes samples from a population using questionnaire. The data analysis method was used is multiple regression analysis. The results of this research are: (1) the compentasion has an effect toward the performance and (2) the work motivation has an effect toward the officer performance as well. The result showed that : (1) The perceived compensation has a positive and significant influence on employee performance in The women empowerment service, child peotection, population control and family planning Board Officer Seluma District, (1) The perceived motivation has a positive and significant influence on employee performance in The women empowerment service, child peotection, population control and family planning Board Officer Seluma District.